SOSIALISASI AKTA KELAHIRAN DI KOTA PONTIANAK - Petrus Yansen Kaligis E.42008054 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
This research slated to describe communication strategy on duty demography and CivilRegistry in birth certificate socialization at City New Town sub-district Pontianak. This paper title isappointed according to about problem reducing the birth certificate ownership zoom on society inparticular sub-district society citizen New Town. This research utilize kualitatif's approximate methodsand analisis SWOT's method. Purpose methodics analisis this aims to reveal supporting factor, resistor,opportunity and faced threat on duty demography and Civil Registry in perform birth certificatesocialization. Supporting factor, interference, opportunity and found threat get on duty been utilizeddemography and Civil Registry as institution of demography administration executor in plotcommunication strategy would be convenient and can minimize possible will its happening aninterference and also threat. Elements that regard communication strategy is Who (Who is itsCommunicator), says what (send away for what does be declared for), in which channel (media that isutilized), to whom (who is its communicant), and with what effect (impact what does be expected).Communication strategy that is done aims to change perception, increase agog and societyparticipation about importance of birth certificate ownership. Keyword : Communication strategy, Birth certificate socialization